PENGGUNAAN SUMBERDAYA OPTIMAL PADA PRODUKSI KOPI DI INDUSTRI 3 BINTANG KOPI KAILI DESA TINGGEDE KECAMATAN MARAWOLA KABUPATEN SIGI - Putri Fillia Indah Anastasya Podala; Arifuddin Lamusa; Dafina Howara (Universitas Tadulako, 2022)
This study aims to determine the optimal use of resources for coffee production and to determine the maximum profit of coffee production obtained by the 3 Bintang Kopi Kaili industry. Respondents were determined. The respondents were determined purposively, with a total of 3 respondents. The analysis used is analysis. The data analysis used is Linear Programming analysis with the help of LINDO software. The results of the study which were calculated using linear program data analysis and assisted by the LINDO application showed that the maximum production was by producing 1000 gram packaged ground coffee with 0,5 kg of raw materials from the total use of 41,66 kg of raw materials, 8,1 workers HOK from the total available workforce of 67.5 HOK, and engine capacity of 24,3 from the total availability of 202,5 engine capacity. The results of this study stated that the production of 100 gram packaged ground coffee was less profitable. The results of this study also show that the 3 Bintang Kopi Kaili industry will get the maximum profit by only producing 100 packs of 1000 gram ground coffee which increases the income by IDR 24.726380 previously the 3 Bintang Kopi Kaili industry only earned a profit of IDR 3.205337.